Satisfaction with Life and Service Delivery in Eastern Europe and the Former Soviet Union : Some Insights from the 2006 Life in Transition Survey - Zaidi, Salman (World Bank, 2012)
The main objective of the Life in Transition Survey (LiTS) was to assess the impact of transition on people, and so the survey questionnaire covered four main themes. First, it collected personal information on aspects of material well-being, including household expenditures, possession of consumer goods such as a car or mobile phone, and access to local public services and utilities. Second, the survey included measures of satisfaction and attitudes towards economic and political reforms as well as public service delivery. Third, the LiTS captured individual 'histories' through transition from around 1989 to the present, especially key events and episodes that may have influenced their attitudes towards reforms, and collected information on individuals; family background, on their employment situation, and on coping strategies during transition. Finally, the survey also attempted to capture the extent to which crime and corruption are affecting peoples' lives, and the extent to which individuals' trust in other people and in state institutions has changed over time. This volume presents the main findings of three studies by World Bank economists using data from the 2006 LiTS. Chapter one examines quantitative and qualitative dimensions welfare in countries of Eastern Europe and the former Soviet Union, with 'satisfaction with life' being the key welfare measure used. Chapter two analyzes socioeconomic characteristics of different income groups across countries, and shows how the welfare measure derived from the LiTS provides a very useful and effective means to measure household welfare and/or rank households by relative economic status, both within as well as across countries. Finally, chapter three focuses on three interlinked questions: (i) why are some people more likely than others to use publicly provided health services? (ii) What are some of the key influences on users' satisfaction with quality and efficiency of medical treatment received? And (iii) how does the prevalence of informal payments impact people's decision on using publicly provided health services, and upon use, the level of satisfaction with services received?